Kualitas Tulang Tikus Betina Normal yang Diberi Ekstrak Sipatah-patah pada Masa Pertumbuhan - Mustafa, Sabri; -, Nurhidayat; Sigit, Koeswinarning; Pontjo Priosoeryanto, Bambang; Manalu, Wasmen (Jurnal Veteriner, 2012)
The experiment was designed to study the effects of sipatah-patah extract (ESP) on bone growth ingrowing female rats in order to prevent osteoporosis during postmenopausal period. Twenty growing femaleSprague Dawley rats in similar body weight were used with the average of age was 20 days old. Theexperimental rats were randomly divided into 5 (five) groups: control group (NOV-0, administered carboxylmethyl cellulose 1%) and groups administered ESP at the age of 30 days (NOV-1), 60 days (NOV-2), 90days (NOV-3), and 120 days (NOV-4) with dosage of 750 mg/kg body weight daily. Blood samples werecollected every 30 days to analyze serum calcium and phosphate concentrations. At the end of the treatment(180 day old), all of the animals were sacrificed to measure and analyze bone growth histologically. Ostibia-fibula slice was stained by using Hematoxylin Eosin (HE) method to observe osteoblast and osteoclastdensities, while Masson trichrome was used to observe trabeculae structure. The results showedadministration of ESP in rat during growing period improved bone growth. NOV-1 with longer duration(150 days) showed better growth rate with longer femur, optimum serum calcium, and phosphateconcentrations, and higher number of osteoblast with lower osteoclast densities compared to control rats(NOV-0). It was concluded that giving ESP at earlier age with longer duration during growth period couldimprove bone growth. This condition was expected could also improve the bone conditions during growingperiod.
Keywords: sipatah-patah extract, osteoblast, osteoclast, trabeculae, serum calcium and phosphate.